Continuous blood purification treatment for endotoxin-induced acute respiratory distress syndrome - Jiang,Y. (2017)
This study aimed to explore the effects of continuous blood purification (CBP) treatment in pigs affected with acute respiratory distress syndrome (ARDS). A total of 12 healthy male pigs, weighing 12±1.8 kg, were randomly and equally assigned to the control and experimental groups. The ARDS pig model was prepared by intravenous injections of endotoxin (20 µg/kg). The control group was given conventional supportive therapy, while the experimental group was given continuous veno-venous hemofiltration therapy. During the treatment process, the variations in dynamic lung compliance, oxygenation index, hemodynamics, and urine volume per hour at different times (Baseline, 0, 2, 4, and 6 h) were recorded. The levels of tumor necrosis factor (TNF-α), interleukin 6 (IL-6), and IL-10 in serum and bronchoalveolar lavage fluid (BALF) were measured using the enzyme-linked immunosorbent assay. The histomorphological changes of the lung, heart, and kidney were visualized using a light microscope. The nuclear factor κB p65 protein content of the heart, lung, and kidney tissues was also detected using western blot. The experimental group outperformed the control group in both respiratory and hemodynamic events. CBP treatment cleared TNF-α, IL-6, and IL-10 partially from serum and BALF. The pathological examination of the heart, lung, and kidney tissues revealed that the injury was less severe in the experimental group. CBP treatment can improve the organ functions of pigs affected with endotoxin-induced ARDS and protect these organs to some extent.